Mypimes of Garzón enter the e-commerce business - Rincón-Vieda, Paulo Andrés
The municipality of Garzón Huila has dabbled with information technology through training processes having the Sena Garzón (Centro Agroempresarial y Desarrollo Pecuario del Huila) an applicative training project Web E-commerce for purchases was developed, in which They benefited six (6) companies where they can market their products anywhere in the world remain competitive in the e-commerce sector.